2022
DOI: 10.3390/pharmaceutics14081543
|View full text |Cite
|
Sign up to set email alerts
|

Dry Powder Comprised of Isoniazid-Loaded Nanoparticles of Hyaluronic Acid in Conjugation with Mannose-Anchored Chitosan for Macrophage-Targeted Pulmonary Administration in Tuberculosis

Abstract: Marketed dosage forms fail to deliver anti-tubercular drugs directly to the lungs in pulmonary Tuberculosis (TB). Therefore, nanomediated isoniazid (INH)-loaded dry powder for inhalation (Nano-DPI) was developed for macrophage-targeted delivery in TB. Mannosylated chitosan (MC) and hyaluronic acid (HA) with an affinity for the surface mannose and CD44 receptors of macrophages were used in conjugation to prepare hybrid nanosuspension by ionic gelation method using cross-linker, sodium tri-polyphosphate (TPP) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…During hemostasis, CS can induce the aggregation of platelets and plasma proteins to help the blood clotting and vasoconstriction at the injured site [ 64 , 65 , 66 , 67 ]. Moreover, CS has been found to enhance the function of polymorphonuclear leukocytes, macrophages, and fibroblasts [ 68 ]. In a study, CS was found to promote the production of hyaluronic acid at the injury site, which induced wound healing faster [ 69 ].…”
Section: Hemostatic Mechanism Of Cs Hydrogelsmentioning
confidence: 99%
“…During hemostasis, CS can induce the aggregation of platelets and plasma proteins to help the blood clotting and vasoconstriction at the injured site [ 64 , 65 , 66 , 67 ]. Moreover, CS has been found to enhance the function of polymorphonuclear leukocytes, macrophages, and fibroblasts [ 68 ]. In a study, CS was found to promote the production of hyaluronic acid at the injury site, which induced wound healing faster [ 69 ].…”
Section: Hemostatic Mechanism Of Cs Hydrogelsmentioning
confidence: 99%
“…The drug delivery to intracellular Mtb in macrophages can be targeted by altering the physicochemical and surface characteristics of nanoparticles and by adapting a hybrid nano-approach, i.e., by using polymers that act as ligands and target specific receptors [ 43 ]. Mukhtar M et al demonstrated the promising anti-TB activity of mannosylated-chitosan and hyaolorunic-acid nanoparticles containing isoniazid, which targeted the CD44 and mannose receptors of macrophages [ 55 ]. The novel MmpL3 (mycobacterial membrane protein large 3) inhibitors, BM625 and BM819, in nanoemulsion and niosomes, showed potent antimycobacterial activity against Mtb [ 56 ].…”
Section: Nanomedicine In Tbmentioning
confidence: 99%
“…The research indicate that the mannosylated models are an effective and safe approach to treating tuberculosis. 216 Mannosylated chitosan nanoparticles conjugated hyaluronic acid (HA) that loaded with isoniazid were synthesized by Mukhtar et al in 2022 and successfully used as an inhalation powder for the treatment of TB. 217…”
Section: Mycolic Acidmentioning
confidence: 99%